Transient Facial Nerve Palsy After Occipital Nerve Block: A Case Report. Issue 10 (10th June 2014) - Strauss, Lauren; Loder, Elizabeth; Rizzoli, Paul
Abstract : Occipital nerve blocks are commonly performed to treat a variety of headache syndromes and are generally believed to be safe and well tolerated. We report the case of an otherwise healthy 24‐year‐old woman with left side‐locked occipital, parietal, and temporal pain who was diagnosed with probable occipital neuralgia. She developed complete left facial nerve palsy within minutes of blockade of the left greater and lesser occipital nerves with a solution of bupivicaine and triamcinolone. Magnetic resonance imaging of the brain with gadolinium contrast showed no abnormalities, and symptoms had completely resolved 4‐5 hours later. Unintended spread of the anesthetic solution along tissue planes seems the most likely explanation for this adverse event. An aberrant course of the facial nerve or connections between the facial and occipital nerves also might have played a role, along with the patient's prone position and the use of a relatively large injection volume of a potent anesthetic. Clinicians should be aware that temporary facial nerve palsy is a possible complication of occipital nerve block.